A randomised control study comparing the Infant Flow Driver with nasal continuous positive airway pressure in preterm infants. Issue 2 (1st September 2001) - Mazzella, M; Bellini, C; Calevo, M G; Campone, F; Massocco, D; Mezzano, P; Zullino, E; Scopesi, F; Arioni, C; Bonacci, W; Serra, G
Abstract : OBJECTIVE: To compare the effectiveness of the Infant Flow Driver (IFD) with single prong nasal continuous positive airway pressure (nCPAP) in preterm neonates affected by respiratory distress syndrome. DESIGN: Randomised controlled study. PATIENTS: Between September 1997 and March 1999, 36 preterm infants who were eligible for CPAP treatment were randomly selected for either nCPAP or IFD and studied prospectively for changes in oxygen requirement and/or respiratory rate. The requirement for mechanical ventilation, complications of treatment, and effects on mid-term outcome were also evaluated. RESULTS: Use of the IFD had a significantly beneficial effect on both oxygen requirement and respiratory rate (p < 0.0001) when compared with nCPAP. Moreover, O2 requirement and respiratory rate were significantly decreased by four hours (p < 0.001 and p < 0.03 respectively). The probability of remaining supplementary oxygen free over the first 48 hours of treatment was significantly higher in patients treated with the IFD than with nCPAP (p < 0.02). IFD treated patients had a higher success (weaning) rate (94% v 72 %) and shorter duration of treatment (49.3 (31) v 56 (29.7) hours respectively; mean (SD)), although the difference was not significant. CONCLUSIONS: IFD appears to be a feasible device for managing respiratory distress syndrome in preterm infants, and benefits may be had with regard to oxygen requirement and respiratory rate when compared with nCPAP. The trend towards reduced requirement for mechanical ventilation, shorter clinical recovery time, and shorter duration of treatment requires further evaluation in a multicentre randomised clinical trial.